Impacts of underwater noise on marine vertebrates: Project introduction and first results - Liebschner, A.; Seibel, H.; Teilmann, J.; Wittekind, D.; Parmentier, E.; Dähne, M.; Dietz, R.; Driver, J.; van Elk, C.; Everaarts, E.; Findeisen, H.; Kristensen, J.; et al. (2016)
© Springer Science+Business Media New York 2016.The project conducts application-oriented research on impacts of underwater noise on marine vertebrates in the North and Baltic Seas. In distinct subprojects, the hearing sensitivity of harbor porpoises and gray seals as well as the acoustic tolerance limit of harbor porpoises to impulsive noise from pile driving and stress reactions caused by anthropogenic noise is investigated. Animals are equipped with DTAGs capable of recording the actual surrounding noise field of free-swimming harbor porpoises and seals. Acoustic noise mapping including porpoise detectors in the Natura 2000 sites of the North and Baltic Seas will help to fully understand current noise impacts.